Comparative Efficacy of Homoeopathic and Antibiotic Growth Promoters on Performance of Commercial Broiler Chicken - B. Gameti, Chintan; P. Savaliya, Fulabhai; G. Mali, Avinash; B. Patel, Atul; J. Bhagora, Nikesh; A. Shekh, Maqbul (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The application of antibiotics as growth promoter in poultry has been banned, hence alternative growth promoters are required to be used. One of them is Homoeopathic remedies. The present study was conducted to evaluate the effect of Homoeopathic and Antibiotic growth promoters on growth performance and feed efficiency of commercial broiler chicken. A total of 144 straight-run day-old commercial broiler chicks were randomly distributed to three treatments (T1, T2, T3). Each treatment consisted of eight replicates and in each replicate, six chicks were there, leading to 48 chicks per treatment. Birds in T1 (Control), received basal diet, while birds of T2 group were provided with Antibiotic Growth Promoters (AGP, Avilamycin, 10 g/100 kg) through feed and T3 group provided with Homoeopathic Growth Promoter (HGP, 2 mL/L) through drinking water. Up to 6 weeks of age, the body weight in birds of control group was significantly (p